(
x
−
1
)
2
+
∣
x
−
1
∣
+
∣
(
x
2
)
+
x
−
2
∣
=
0
x
is real. Find
x
.
Hint: square of real number is always positive.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since the term ( x − 1 ) 2 can be rewritten as the product of identical terms in absolute value signs, and ∣ ∣ x 2 + x − 2 ∣ ∣ = ∣ x + 2 ∣ ∣ x − 1 ∣ , then we can rewrite the equation to the following form.
( x − 1 ) 2 + ∣ x − 1 ∣ + ∣ ∣ x 2 + x − 2 ∣ ∣ = ( ∣ x − 1 ∣ ) 2 + ∣ x − 1 ∣ + ∣ x + 2 ∣ ∣ x − 1 ∣
Factoring out ∣ x − 1 ∣ , we can solve for x.
∣ x − 1 ∣ ( ∣ x − 1 ∣ + 1 + ∣ x + 2 ∣ ) = 0
Since the sum of the terms in parentheses can't be equal to 0, then it must be that x = 1 .
Let a = (x-1)^2, b = | x - 1 |, c = | x^2 + x -2 |. All terms (a, b, c) are positive so their summation can only be zero if each is zero. x=1 yields zero for each of the terms a,b, and c.
every time it need not be that their summation is 0 only IF EACH IS ZERO. it can also be that one is negative and other possitive even then they will be summing up to 0 only
Log in to reply
Did you notice the | | sign of the last two terms and the square of the first term. Hence all the three terms should be >= 0. Given that they are real and their summation =0, each of them must be zero
Since the RHS is 0 the sum of the terms on the LHS is 0 and therefore all three terms must be 0. And x = 1 is the only value that solves the equation.
So easy ... Just substitue x = 1 into the equation : ( x − 1 ) 2 + ∣ x − 1 ∣ + ∣ ( x 2 ) + x − 2 ∣ = 0 ( 1 − 1 ) 2 + ∣ 1 − 1 ∣ + ∣ 1 2 + 1 − 2 ∣ = 0
( 0 ) 2 + ∣ 0 ∣ + ∣ 1 − 1 ∣ = 0
0 = 0
So we get x = 1
Each and every part inside the modulus sign is >=0 so we can say that it will be equal to 0 if we have (x-1)²=0
As all the terms are positive and summing up of the positive terms can not be zero, so we have to make all terms equal to zero.....So we can say x-1=0 =>x=1.
Since each quantities are positive each of them must be 0. The only number for each quantity which makes them 0 is 1. x-1=0 and x=1
Problem Loading...
Note Loading...
Set Loading...
All of the quantities are within absolute value signs. Thus if any of those quantities within the absolute value signs are anything other than 0, then the equation will not be true because anything in absolute value signs are either 0 or positive. Therefore x - 1 must equal zero.
Thus we can set x − 1 = 0 , so x must be 1.
Note that if you set x 2 − x − 2 = 0 equal to zero, the -2 that we get as a solution is extraneous.
X = 1